Molecular Classification in Patients With Endometrial Cancer After Fertility-Preserving Treatment: Application of ProMisE Classifier and Combination of Prognostic Evidence - Ran, Xuting; Hu, Tingwenyi; Li, Zhengyu (Frontiers in Oncology, 2022)
The Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) is a molecular classification system that identifies endometrial cancer (EC) into four prognostically distinct subtypes: POLE-mutated, mismatch repair deficiency (MMR-D), p53 wild type (p53wt), and p53 abnormal (p53abn). However, few reports have applied ProMisE classifier to EC patients who underwent fertility-preserving treatment (FPT) so far. This study aimed to evaluate whether ProMisE classifier prognosticates in early-stage EC patients after FPT. We first summarized the three reported outcomes of ProMisE applied in EC patients received FPT. Hormone-treated patients with EC from 2010 to 2020 in our facility were then analyzed. Patients’ formalin-fixed paraffin-embedded blocks before treatment were collected and classified into POLE-mutated, MMR-D, p53wt and p53abn subtypes, by sequential immunohistochemistry and Sanger sequencing of POLE according to the ProMisE system. The primary outcome was response rate after FPT. 13 patients were enrolled from our facility, with 3 (3/13) MMR-D, 0 (0/13) POLE, 8 (8/13) p53wt, 1 (1/13) p53abn and 1 (1/13) failed with DNA amplification. 6 (6/8) patients with p53wt, 2 (2/3) patients with MMR-D, and 1(1/1) patient with p53abn achieved complete response in 6 months after treatment. Results of our study and reported outcomes were combined finally. A total of 106 patients underwent FPT were included. Of these, 23 (21.7%) were classified as MMR-D, 3 (2.8%) as POLE-mutated, 3 (2.8%) as p53abn and 77 (72.6%) as p53wt. No significant difference in the response rate (P=0.152) and recurrence rate (P=0.174) between MMR-D and p53wt subtypes after FPT. Based on current data, we observed no prognostic significance of ProMisE classifier in EC patients underwent FPT. Larger prospective studies are needed to elucidate the precise prognostic meaning of this molecular classifier in the cases.